Multidisciplinary research into the topography and landscape of Roman Rider (Danilo, Šibenik, Croatia) – first results of the excavations near St. Daniel’s church and new data on the medieval cemetery at Šematorij site - Rabiega, Kamil; Konestra, Ana; Krnčević, Željko; Brajković, Toni (Saeculum Christianum, 2025)
The village of Danilo, located in the southern part of Šibenik-Knin County, is known for several archaeological sites where research is conducted since 1951. Among these, at the location Šematorij/Stari Šematorij the remains of a large Roman building (villa?) and thermae dating back to the 1st or early 2nd century were discovered. The ancient roots of the village are evidenced by inscriptions mentioning the Roman city of Rider (Municipium Riditarum), founded in the second half of the 1st century. Near the 18th-century church of St. Daniel, archaeologists have been finding numerous architectural elements and decorations from the interior of a monumental Roman building for years, but the precise location of it were unknown until recently. The conducted geophysical research, analysis of LiDAR data and archaeological excavations suggest that the area currently occupied by the church and the extensive cemetery might conceals the remains of the ancient center of the Roman town of Rider. Wieś Danilo, położona w południowej części żupanii szybenicko-knińskiej, znana jest z kilku stanowisk archeologicznych, na których badania prowadzone są od 1951 roku. Wśród nich, w lokalizacji Šematorij/Stari Šematorij odkryto pozostałości dużej rzymskiej budowli (willi?) i term datowanych na I lub początek II wieku. O starożytnych korzeniach wioski świadczą inskrypcje wspominające rzymskie miasto Rider (Municipium Riditarum), założone w drugiej połowie I wieku. W pobliżu XVIII-wiecznego kościoła św. Daniela archeolodzy od lat znajdują liczne elementy architektoniczne i dekoracje z wnętrza monumentalnej rzymskiej budowli, jednak jej dokładna lokalizacja do niedawna była nieznana. Przeprowadzone badania geofizyczne, analiza danych LiDAR i wykopaliska archeologiczne wskazują, że obszar zajmowany obecnie przez kościół i rozległy cmentarz może kryć pozostałości starożytnego centrum rzymskiego miasta Rider.